Optimization and Economic Analysis of Green Public Building Envelope Structure in Chongqing - Yang, Zhiwei; Chen, Jihuan; Lei, Xilin; Lin, Xinran; Zhang, Shaoting (Journal of Basic & Applied Sciences, 2023)
This article entitled "Optimization and Economic Analysis of Green Public Building Envelope Structure in Chongqing", Authors, Zhiwei Yang Jihuan Chen Xilin Lei Xinran Lin and Shaoting Zhang, published in Volume 19, pp. 77-85 retracted by the authors due to serious similarity problem.